Laporan pelaksanaan Kuliah Kerja Nyata (KKN) IAIN Raden Intan, Tanjungkarang
Report of the implementtation of the Student Field Service Program at Raden Intan Institute for Islamic Studies, Tanjungkarang, Propinsi Lampung.